Additional value of T1 and T2 mapping techniques for early detection of myocardial involvement in scleroderma. (1st April 2023) - Meloni, Antonella; Gargani, Luna; Bruni, Cosimo; Cavallaro, Camilla; Gobbo, Marco; D'Agostino, Andreina; D'Angelo, Gennaro; Martini, Nicola; Grigioni, Francesco; Sinagra, Gianfranco; De Caterina, Raffaele; Quaia, Emilio; et al.
Abstract: Background: We evaluated the prevalence of myocardial involvement by native T1 and T2 mapping, the diagnostic performance of mapping in addition to conventional Lake Louise Criteria (LLC), as well as correlations between mapping findings and clinical or conventional cardiovascular magnetic resonance (CMR) parameters in systemic sclerosis (SSc) patients. Methods: Fifty-five SSc patients (52.31 ± 13.24 years, 81.8% female) and 55 age- and sex-matched healthy subjects underwent clinical, bio-humoral assessment, and CMR. The imaging protocol included: T2-weighted, early post-contrast cine sequences, native T1 and T2 mapping by a segmental approach, and late gadolinium enhancement (LGE) technique. Results: Global myocardial T1 and T2 values were significantly higher in SSc patients than in healthy subjects. An increase in native T1 and/or T2 was present in the 62.1% of patients with normal conventional CMR techniques (negative LGE and T2-weighted images). Respectively, 13.5% and 59.6% of patients fulfilled original and updated LLC (overall agreement = 53.9%). Compared with patients with normal native T1, patients with increased T1 (40.0%) featured significantly higher left ventricular end-diastolic volume index and cardiac index, biventricular stroke volume indexes, and global heart T2 values, and more frequently had a history of digital ulcers. Biochemical and functional CMR parameters were comparable between patients with normal and increased T2 (61.8%). Conclusion: T1 and T2 mapping are sensitive parameters that should be included in the routine clinical assessment of SSc patients for detecting early/subclinical myocardial involvement. Graphical abstract: Unlabelled Image Highlights: In patients with systemic sclerosis myocardial T1 and T2 mapping can detect early/subclinical myocardial involvement. In systemic sclerosis the mapping techniques have an additional value compared to conventional non-parametric CMR indices. Systemic sclerosis patients with an history of digital ulcers were more likely to have an increased global heart T1 value.